Ibuprofen enhances synaptic function and neural progenitors proliferation markers and improves neuropathology and motor coordination in Machado–Joseph disease models. (25th May 2019) - Mendonça, Liliana S; Nóbrega, Clévio; Tavino, Silvia; Brinkhaus, Maximilian; Matos, Carlos; Tomé, Sandra; Moreira, Ricardo; Henriques, Daniel; Kaspar, Brian K; Pereira de Almeida, Luís
Abstract: Machado–Joseph disease or spinocerebellar ataxia type 3 is an inherited neurodegenerative disease associated with an abnormal glutamine over-repetition within the ataxin-3 protein. This mutant ataxin-3 protein affects several cellular pathways, leading to neuroinflammation and neuronal death in specific brain regions resulting in severe clinical manifestations. Presently, there is no therapy able to modify the disease progression. Nevertheless, anti-inflammatory pharmacological intervention has been associated with positive outcomes in other neurodegenerative diseases. Thus, the present work aimed at investigating whether ibuprofen treatment would alleviate Machado–Joseph disease. We found that ibuprofen-treated mouse models presented a significant reduction in the neuroinflammation markers, namely Il1b and TNFa mRNA and IKB-α protein phosphorylation levels. Moreover, these mice exhibited neuronal preservation, cerebellar atrophy reduction, smaller mutant ataxin-3 inclusions and motor performance improvement. Additionally, neural cultures of Machado–Joseph disease patients' induced pluripotent stem cells-derived neural stem cells incubated with ibuprofen showed increased levels of neural progenitors proliferation and synaptic markers such as MSI1, NOTCH1 and SYP. These findings were further confirmed in ibuprofen-treated mice that display increased neural progenitor numbers (Ki67 positive) in the subventricular zone. Furthermore, interestingly, ibuprofen treatment enhanced neurite total length and synaptic function of human neurons. Therefore, our results indicate that ibuprofen reduces neuroinflammation and induces neuroprotection, alleviating Machado–Joseph disease-associated neuropathology and motor impairments. Thus, our findings demonstrate that ibuprofen treatment has the potential to be used as a neuroprotective therapeutic approach in Machado–Joseph disease.